Alpha-glucosidase Inhibitory Activity in Methanol Extract of some Plants from Kurdistan Province - Mohammad Ali Zarei; Hassan Tahazadeh (Institue of Medicinal Plants, ACECR, 2019)
Background: Since the alpha-glucosidase enzyme degrades complex carbohydrates and opens the way for their subsequent absorption and increases blood glucose levels, inhibitors of this enzyme are used as drugs for the treatment of some forms of diabetes.One of the medical treatments that have been given so much attention throughout the world is herbal medicine. Therefore, plants are a very good source of bioactive compounds. Objective: The aim of this study was to find strong and new inhibitors of alpha-glucosidase enzymes using plant sources. Method: Methanolic extracts of 32 plant species collected from central regions of Kurdistan province were investigated for their inhibitory activity on alpha-glucosidase enzymes at concentrations of 1, 0.1, 0.01 and 0.001 mg / ml. Acarbose was used as a positive control. All measurements were performed in three replications. Results: According to the results of this study, the extracts of Campanula involucrata Auch .ex DC, Hypericum scabrum L., Salvia suffruticosa Montbr. & Auch and Silene ampulata Bioss. showed inhibitory activities greater than 60% on the alpha-glucosidase enzyme. The inhibitory activity of the extract of Campanula involucrata and Silene ampulata was significantly higher, and their IC50 was 0.02 mg / ml. Conclusion: Therefore, it can be concluded that the just-mentioned plants extract, due to the high inhibition rate and low IC50, can be an interesting topic for more accurate studies.